Genetic divergence among Eucalyptus tereticornis Smith open pollinated progenies for growth and wood quality characters - Zanatto, Bruna [UNESP]; de Paula, Rinaldo Cesar [UNESP]; de Paula, Nádia Figueiredo; Freitas, Miguel Luiz Menezes; de Araújo, Marcio José [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
Eucalyptus tereticornis Smith has good adaptability to different regions and drought resistance, presenting fast growth and great potential of wood for different uses. In Brazil, there are few studies with this species, needing to evaluate the genetic divergence between the accessions available in provenances and progeny tests spread throughout the country. In this sense, the present work aimed to evaluate the genetic divergence between open-pollinated progenies of E. tereticornis based on wood growth and chemical traits. The experiment was carried out near the town of Luiz Antônio (SP), with 30 progenies of E. tereticornis, belonging to two origins. At 31 years of age, diameter at breast height, total height, commercial volume with bark, trunk biomass, basic density (DBM), cellulose (CEL), lignin (LIG), extractives (EXT) and holocellulose (HOLO) contents in wood. Three representative trees of each progeny were selected to determine the volume and obtain discs in different stem positions to determine the chemical wood traits. Multivariate analysis was performed by the Ward hierarchical method and non-hierarchical K-means (K-means) and the principal component analysis from the correlation matrix. By Ward's method, the progenies were divided into three groups, and groups 1 and 2, with higher yields, differed by the chemical wood traits from group 3, which presented a lower productivity. By the K-means method, the three groups differed little from those obtained by the Ward method, but had better defined traits. In the principal component analysis the first three components explained 78.76% of the variance contained in the original variables. In general, the chemical wood traits showed a quasi-independence of the tree growth potential. The highlighted characters in the three main components are of great importance for selecting the most promising progenies for a breeding program. The main component 1 (CP1) is related to the progeny productivity, CP2 with LIG and HOLO and CP3 with DBM and CEL. The presence of genetic divergence among the 30 open pollinated progenies of Eucalyptus tereticornis is not related to seed origin. The progenies evaluated differed in the productive potential and quality of wood traits. The identified groups can be used in breeding strategies in order to select superior progenies for genetic gain in productivity and wood quality improvement for different segments, according to the breeding program objective.
Divergência genética entre progênies de polinização aberta de Eucalyptus tereticornis Smith para caracteres de crescimento e de qualidade da madeira
Keywords: Forest improvement; Multivariate analysis; Wood quality